Preventing Violence in the Disability Margins: A Culture-Centered Study in Aotearoa - Dutta MJ; Elers P; Zorn A; Brey S; Metuamate S; Pokaia V; Jayan P; Rahman M; Hashim S; Liu J; Nematollahi N; Sharif ASBM; et al. (y Oxford University Press on behalf of International Communication Association, 2025)
Disabled people are overrepresented as victims of sexual violence and family violence, but are often excluded from research and the development of communication campaigns, laws, and interventions. Grounded in the culture-centered approach, we undertook 77 qualitative interviews with predominantly Māori (Indigenous) and low-income disabled individuals to identify primary prevention needs for reducing family and sexual violence. Participants articulated disability as being structural, intersectional, and layered with erasure, contributing to conditions that perpetuate violence. Erasure and the resulting loss of agency were pervasive across diverse disabilities and participant groups, with Māori bearing a disproportionate burden. Emergent in the participants’ narratives were strategies around addressing communication inequalities and grounding prevention resources within local community contexts, set against structural determinants of violence perpetuated by the settler colonial State. This study challenges the hegemonic approach to addressing sexual violence and family violence, revealing a relationship between communicative and material forms of violence.
Keywords: violence prevention; communication inequality; culture-centered approach; disability communication